Optimization Parameters of Natural Deep Eutectic Solvent Based on Choline Chloride and Fructose for Extraction of Polyphenol from Jotang (Spilanthes acmella) Stem - Putri, Fajar Amelia Rachmawati; Maimulyanti, Askal; Nurhidayati, Isna; Mellisani, Bella; Widarsih, R. Wiwi; Puspita, Fitria; Prihadi, Anton Restu (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2024)
Natural deep eutectic solvents (NADES) have become popular as an environmentally benign alternative to conventional solvents for extracting natural compounds. In this current research, choline chloride was employed as a hydrogen bond acceptor (HBA) and was mixed with fructose which had the role of a hydrogen bond donor (HBD) to construct NADES. This extracting agent was deployed to separate the polyphenolic compounds from the stem of Jotang (Spilanthes acmella) under prime conditions. The extracted polyphenol was subsequently calculated based on the Folin-Ciocalteu method using gallic acid as the standard solution by UV-Vis spectrophotometer at 760 nm. Corresponding to the research outcomes, the most gainful states of extraction were achieved at a sample weight-to-NADES volume ratio of 1:50, a period of extracting process of 60 min, water content of 20%, and a stirring speed of 80 rpm. The optimized parameters were conceived as the most gainful because they exhibited the most prominent level of polyphenol were described as follows: ratio of sample weight-to-NADES volume and extraction time showed polyphenol content of 25.13 mg GAE/g each, while the others, stirring speed and water content revealed the polyphenol concentration of 25.75 mg GAE/g respectively.